Evaluation and prediction of high-quality development in China: A time-spatial analysis from Hubei province - Huang, Jin; Tian, Ye; Khanal, Ribesh; Wen, Faguang; Deng, Chaohui (Frontiers in Environmental Science, 2022)
The common goal of all countries is to improve social and economic growth in a methodical and sustainable manner. Following years of rapid urbanization and industrialization, China is on the verge of transitioning from rapid to high-quality development. Building a scientific high-quality index system, calculating and forecasting high-quality development status of one region could help the government's long-term growth strategy. In our paper, with data from 2010 to 2020 of Hubei province in central China as an example, we firstly designed high-quality system that combines economic, social, and environmental dimensions, secondly applied information entropy to calculate high-quality development efficiency, and then adopted the BP neural network method to simulate the development trend. Results reveal that: (1) According to the research sub-index findings, the opening and innovation indicators have the highest weights of 0.379 and 0.278, respectively. Economic growth, on the other hand, weighed in at 19.2 %, while coordination, sustainability, and sharing all weighed in at less than 10%. (2) From 2010 to 2020, Wuhan's average comprehensive index was greater than 0.5, seven times that of second-place Xiangyang and 46 times that of last-place Shen Nongjia. In conclude, the comprehensive index revealed that the high-quality growth of different cities in Hubei Province is insufficient and unequal. (3) With the uncontrolled situation such as COVID-19, Hubei province projected results for high-quality growth for 2021-2025 is on decline, and it is expected to decrease by 5% on average starting in 2019. Based on the findings, we urge that the government to expand technical innovation, adapt policy relevant, promote ecological economy growth, and improve people's well-being to achieve long-term high-quality development.